International news flow online global views with local perspectives - Segev, Elad (Mass communication and journalism, 2016)
The book explores the theory of news flow around the world, and analyses many of its dimensions such as the global standing of the United States, the Middle Eastern conflicts as seen around the world, and, the effect of financial news. In doing so, the book unveils new patterns, meanings and implications of international news on our perception of the world.